Study of light weight composite concrete incorporated with Polypropylene fiber and Cenosphere. (2022) - Jeyanthi, J.; Revathi, S.
Abstract: The Composite Concrete is used as Supplementary Construction materials to enhance the performance of the construction materials in the current scenario. Also, the rapid growing demand of the concrete has increased the environmental pollution. Hence, there is a need of the supplementary cementitious materials (SCM). Cenophhere is one of the SCM, which is a lightweight, inert, hollow sphere having silica and alumina. The fibers are the reinforcement incorporated in the concrete to improve the mechanical properties. The Polypropylene fiber is chosen and the Significance of Cenosphere and Polypropylene (PP) fiber combination in concrete are explored in this study. The various proportions of cenosphere (0%, 15%, and 30%) are combined with 0.5 % Polypropylene fiber to find the optimum Mechanical properties for the Composite concrete. The composite Concrete is determined as Light weight concrete with the use of Cenosphere and Polypropylene fiber. The Micro structural Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) analysis of Cenosphere shown its hollow nature and polypropylene fiber shows that it has non sticky nature which contribute to the light weight for the composite concrete.